2014
DOI: 10.1186/1756-0500-7-653
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of Widal test with blood culture in the diagnosis of typhoid fever in febrile patients

Abstract: BackgroundTyphoid fever is a major health problem in developing countries and its diagnosis on clinical ground is difficult. Diagnosis in developing countries including Ethiopia is mostly done by Widal test. However, the value of the test has been debated. Hence, evaluating the result of this test is necessary for correct interpretation of the result. The main aim of this study was to compare the result of Widal test and blood culture in the diagnosis of typhoid fever in febrile patients.MethodsBlood samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
89
6
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 13 publications
13
89
6
4
Order By: Relevance
“…This high positive result in Widal slide agglutination test may be associated with cross-reacting antibodies from serum of febrile patients other than typhoid fever. Low proportion of Widal test was observed in studies conducted in Ethiopia (32.6%) 24 and Nigeria (55%), 25 as compared with the current finding. This difference might be due to difference in sociodemographic status, immune status, and antibody that cross-reacts with S. enterica serotype Typhi during infection.…”
mentioning
confidence: 35%
“…This high positive result in Widal slide agglutination test may be associated with cross-reacting antibodies from serum of febrile patients other than typhoid fever. Low proportion of Widal test was observed in studies conducted in Ethiopia (32.6%) 24 and Nigeria (55%), 25 as compared with the current finding. This difference might be due to difference in sociodemographic status, immune status, and antibody that cross-reacts with S. enterica serotype Typhi during infection.…”
mentioning
confidence: 35%
“…Reports by the World Health Organization revealed that about 21 million cases and >600,000 annual deaths from typhoid fever occur throughout the world. Developing nations share the highest burden due to rapid population growth, increased urbanization, and limited safe water and health systems [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The same study, using Widal test, also showed that TO antigen was positive (>1/80 dilution) in 47% of febrile patients, and TH antigen was positive in 26% cases (cutoff > 1/160). Positive for both TO and TH were 24.4% 5 . In a similar study, among the total of 67 adult patients clinically marked for typhoid fever, S.typhi was detected in only 8 (11.9%) patients and S.paratyphi A was detected in only 3 (4.5%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Taking diagnosis into concern, enteric fever raises confusion among the Afro-Asian countries. Blood culture technique is the most reliable diagnostic method, but is time consuming and expensive 5 . Detection of the pathogen in blood samples through polymerase chain reaction is probably the best and most reliable method.…”
Section: Introductionmentioning
confidence: 99%